Medication and physical activity and physical fitness in severe mental illness. - Cuesta-Vargas, Antonio; Vera-Garcia, Elisa; Mayoral-Cleries, Fermin; Pérez-Cruzado, David Francisco (Elsevier, 2018)
Anti-psychotic medication has emerged as the primary medical treatment for people with severe mental illness, despite the great risks involved in the use of this medication. In addition, this population suffers from problems of obesity, sedentary lifestyle and poor physical fitness, which is aggravated by the use of this type of medication. The objective of this study is to explore the influence of the most commonly used antipsychotics in this population (Olanzapine and Risperidone) on physical activity and the physical fitness of people with severe mental illness. Sixty-two people between 26 and 61 years of age with severe mental illness were assessed. All participants were evaluated with a battery of 11 physical tests to assess their physical fitness and with the IPAQ-short version questionnaire to determine their level of physical activity. The doses of Risperidone and Olanzapine were also evaluated in all participants. Significant differences were found for physical activity, with higher levels reported in those patients with severe mental illness who did not take any of these medications. Regarding physical fitness, significant differences were only found for the consumption of Risperidone, with better physical fitness levels seen in patients who did not consume this medication; on the other hand, for the consumption of Olanzapine, differences were found in muscular strength, balance and aerobic condition with better values in non-Olanzapine consumers compared with Olanzapine consumers.
https://openpolicyfinder.jisc.ac.uk/id/publication/16060
Keywords: Ejercicio físico - Aspectos psicológicos; Fitness condition; Medication; Physical activity; Physical activity psychiatry; Physical fitness